S116 Hot decaf: a rct comparing home treatment and inpatient care in copd exacerbations selected by low risk decaf score. (15th November 2016) - Echevarria, C; Hartley, T; Gray, J; Muirhead, C; Van-Wersch, A; Miller, J; Steer, J; Simpson, AJ; Gibson, GJ; Bourke, SC
Abstract : Background: The DECAF score is a robust predictor of early mortality in patients admitted with an acute exacerbation of COPD (AECOPD), 1 and should be routinely documented on admission. 2 Of importance, 45–53% of admitted patients are low risk by DECAF (0–1), therefore potentially suitable for hospital at home (HAH). Compared to existing criteria, selection by DECAF would allow inclusion of substantially more patients, some with higher medical dependency. Methods: In a randomised controlled trial (RfPB PB-PG-0213-30105), patients admitted with an AECOPD were allocated to HAH or usual care (UC). Readmissions for AECOPD within 90 days were managed according to the allocated arm, provided they were low risk (DECAF = 0–1). Eligibility criteria included: primary diagnosis AECOPD, DECAF score 0–1, age 35 or more, 10 or more cigarette pack-year history and obstructive spirometry (FEV1/VC less than 70%). Total bed days and readmissions over 90 days, and 14 and 90 day mortality were captured. At day 14, patients were asked for their preferred place of care during future exacerbations of similar severity. Results: Between June 2014 to January 2016 118 of 207 eligible patients were randomised: female = 56/118 (52.5%), mean age (SD) = 69.8 (10.2), mean FEV1% predicted (SD) = 43.9 (17.6) and coexistent pneumonia = 24/118 (20.3%). At 14 days, 105/117 (90%) patients expressed a preference for HAH. Median bed days were 4 days lower in the HAH arm (p = 0.001), with no difference in mortality or readmissions. Conclusions: Selection for HAH by low risk DECAF score is safe, clinically effective, preferred by most patients, reduces total bed days and is a suitable option for up to 50% of admitted patients. References: Steer J, et al . The DECAF Score: predicting hospital mortality in exacerbations of chronic obstructive pulmonary disease. Thorax 2012;67 (11):970–6. BTS national audit report 2015.